Profil psikologis atlet seni bela diri: Kepercayaan diri, agresivitas, motivasi, dan dorongan kompetitif - I Putu Darmayasa; Suratmin Suratmin; Wigutomo Gozali; Ni Putu Vivin Indrawati (Universitas Nusantara PGRI Kediri, 2025)
This study aims to define the psychological profile of martial arts athletes in Bali Province, focusing on self-confidence, adaptive aggression, motivation, and competitive drive as indicators of competition readiness. A quantitative descriptive survey was undertaken with N = 546 athletes participating in regional training programs across 10 martial arts disciplines: Judo, Karate, Kempo, Muay Thai, Pencak Silat, Taekwondo, Tarung Derajat, Boxing, Wushu, and Yongmoodo. Athletes were recruited utilizing selective sampling based on active training status and competitive experience. Data were acquired by standardized psychological surveys and evaluated using descriptive statistics, including frequencies and percentages. The results suggest that self-confidence (86.44%) and motivation (89.93%) were widely evaluated as good to very good. In contrast, adaptive aggression was rather low, with 66.85% of athletes falling in the poor to very poor category. The competitive requirement variable was primarily distributed across the adequate (40.66%) and good (40.11%) levels, with only 11.17% achieving the very good level. Differences were noted between disciplines, with Pencak Silat, Karate, and Tarung Derajat displaying substantially higher psychological profiles. Overall, the data suggest that athletes exhibit high levels of self-confidence and motivation; however, they demonstrate limited growth in adaptive aggression and competitive need. These results reveal an unequal pattern of competitive readiness and provide a baseline for future analytical or longitudinal investigations into the psychological aspects of combat sports.